SISTEM INFORMASI PEMBAYARAN SPP PADA SEKOLAH MENENGAH PERTAMA TRISAKTI 2 MEDAN - Jonathan Hamonangan Saragih; Roni Jhonson Simamora; Resianta Perangin-angin (Universitas Methodist Indonesia, 2022)
An effective tuition payment system will trigger the performance of schools to be better than before. For this reason, it is necessary to have a system that is able to handle the process of paying tuition fees that can help the performance of the school treasurer in his work. Currently, the SPP payment process at Trisakti 2 Medan Catholic Junior High School is still using a manual system by recording it into a booklet and then recaping it in the tuition payment ledger. The problem that arises is that the payment recapitulation process is carried out several times, causing a process that takes a long time to process.